2020
DOI: 10.1016/j.matt.2019.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Anti-solvent-free Spin-Coated and Printed Sn-Perovskite Solar Cells with Crystal-Based Precursor Solutions

Abstract: The existence of a mass oxidation of Sn 2+ that takes place mainly during preparation of precursor solutions and fabrication of films creates a lead-free solar cell of low open-circuit voltage, which leads to low PCE. To reduce the oxidation process, we employed an innovative crystal fabrication method with anti-solventfree recrystallization technology. As a result, to the best of our knowledge, both spin-coated and printed lead-free solar cells based on FASnI 3 achieved the highest 3D-based PCE to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…Because of less redox potential of Sn 2+ absorption layer, oxidation occurs while preparing precursor solution and fabricating perovskite film. Therefore, to reduce the oxidation process and to achieve excellent air stability, two approaches were demonstrated by He et al [58] i.e. crystal-resolving and recrystallization technology.…”
Section: B Fasnx3mentioning
confidence: 99%
See 1 more Smart Citation
“…Because of less redox potential of Sn 2+ absorption layer, oxidation occurs while preparing precursor solution and fabricating perovskite film. Therefore, to reduce the oxidation process and to achieve excellent air stability, two approaches were demonstrated by He et al [58] i.e. crystal-resolving and recrystallization technology.…”
Section: B Fasnx3mentioning
confidence: 99%
“…In another study, where π-conjugated Lewis base strategy was employed using CDTA for the fabrication of FASnI3 based solar cell, the device showed a PCE of 10.32% and maintained over 90% of its initial PCE [64]. Other techniques that have been observed to be successful to improve the stability of formamidinium tin halide perovskites include tin source purification [49], bilateral interfacial engineering strategy [53], orientation regulation process [57], anti-solvent-free spin-coating and inkjet printing [58], bidentate coordination strategy [60], intercalation of PEG into PEDOT:PSS layer [100], etc. CsSnI3 based solar cell with 10% SnCl2 which was fabricated without any HTL demonstrated good stability and efficiency of 3.56% [25].…”
Section: Materials Stabilitymentioning
confidence: 99%
“…Several strategies employing single crystals have been proven to benefit the efficiency and stability, nevertheless, there is rarely a report on LFPSC film-based solar cells, and the photovoltaic parameters of some relevant works are summarized in Table 3. He et al fabricated the device using synthesized FASnI 3 single crystals as precursors, which possessed high purity, low defect density, and excellent stability in the air [59]. The authors demonstrated that re-dissolved single crystals forming solution effectively prevents the oxidation of Sn 2+ by reducing impurities and moisture.…”
Section: Solar Cellsmentioning
confidence: 99%
“…Compared to the oxidation after the device was fabricated, the oxidation during the preparation of precursor solutions and fabrication of films due to the low redox potential of the stannous absorption layer are even more severe. [ 77 ] He et al. discussed that when the oxygen concentration increased, the Sn 4+ ratio of the control sample significantly increased to 31.2% at 10 ppm oxygen and 54.4% at 100 ppm oxygen, indicating that the Sn 4+ defect density in the FASnI 3 film is quite sensitive to the fabrication conditions.…”
Section: Sn‐based Perovskite Solar Cellsmentioning
confidence: 99%
“…employed an innovative crystal fabrication method with anti‐solvent‐free recrystallization technology. [ 77 ] There have been two different kinds of precursors, the first prepared using FASnI 3 crystalline powder diluted in solvent and the second FAI+SnI 2 precursor, as shown in Figures 7 and 8. Then two kinds of perovskite films and devices were fabricated.…”
Section: Sn‐based Perovskite Solar Cellsmentioning
confidence: 99%